نشاط محمد العربي الزبيري ودوره في كتابة تاريخ الجزائر (1941/2024) - عريض إيمان; شراحي بثينة; خضير عائشة (University of Eloued جامعة الوادي, 2025)
"يتناول هذا البحث سيرة المؤرخ والمناضل محمد العربي الزبيري، أحد أبرز الشخصيات الجزائرية في القرن العشرين ودوره المحوري في الكتابة والتأريخ تاريخ الجزائر خاصة خلال الفترة الإستعمار الفرنسي، ركزت دراستنا على عدة محاو، منها السيرة الذاتية: ولد محمد العربي الزبيري ببسكرة ومسقط رأسه سيدي عقبة وتلقي تعليمه بالجزائر، وعمل في الصحافة والتعليم، والكتابة كما شغل مناصب ثقافية وإدارية مهمة بعد الإستقلال، وكما ساهم في النشاط السياسي والثقافي، والكتابة التاريخية أيضا، حيث كانت لديه العديد من المؤلفات خلاصة القول نرى بأن محمد العربي الزبيري ساهم بجهوده الفكرية والأدبية في توثيق الذاكرة الوطنية، وإعادة كتابة التاريخ الجزائري من منظور وطني، وتعد كتاباته مرجعا مهما لفهم الهوية الجزائرية والنضال من أجل الإستقلال. " " This research deals with the biography of the historian and activist Mohamed Larbi Zbiri, one of the distinguished Algerian figures of the twentieth century and a pivotal figure in writing and history, a special history during the French colonial period. Our study focused on the following topics, including the autobiography : Mohamed Larbi Zbiri was born in Biskra and the birthplace of Sidi Okba. He received his education in Alegria and worked in journalism, officially as a job only as an architect and a bureaucrat after independence. He also contributed to political and cultural activity, also in Alegria, where many of the final works were not completed. The final statement is that Mohamed Larbi Zbiri contributed to the Algerian cultural activity, as many of the final works were not completed. That Muhammad al-Arabi al-Zubayri His intellectual and literary efforts contributed to documenting the national memory and rewriting Algerian history from a national perspective. His writings are an important reference for understanding Algerian identity and the struggle for independence. (He contributed through his copyright and literary efforts to the issue of national memory, and wrote Algerian history from my homeland. His book has become a reference for understanding Algerian identity and the struggle for independence.( "
مذكرة ماستر قسم علوم انسانية تخصص تاريخ المغرب العربي المعاصر
Keywords: محمد العربي الزبيري-تاريخ الجزائر-الكتابة التاريخية-النشاط الفكري - الإستعمار- الثورة التحريرية.; Muhammad al-Arabi al-Zubayri - Algerian history - historical writing - intellectual activity - colonialism - liberation revolution.